A Case of Reed Syndrome with a Novel Mutation in the Fumarate Hydratase Gene - Christin B. Laufer; Layne B. Green; Darren E. Whittemore (Case Reports in Medicine)
Reed syndrome is a heritable cancer predisposition syndrome that can easily be missed due to its simple presentation of tender red papules. We present a young female with a history of uterine fibroids who presented to the dermatology clinic with several painful pink papules that had been previously evaluated by multiple physicians. Biopsy results were diagnostic for cutaneous leiomyomas, raising clinical suspicion for Reed syndrome. She was found to have a novel heterozygote mutation in her fumarate hydratase gene, supporting the diagnosis. This case demonstrates the importance of rendering a proper workup for seemingly innocent skin complaints as they could be associated with an underlying malignancy. Despite the fact that up to 16% of patients can develop aggressive type 2 papillary renal cell carcinoma, there are currently no consensus guidelines on screening or patient management.